PT, Department of Physical therapy, Madinah Teaching Hospital Faisalabad - Sahar Ashraf; Nazia Sarfraz (Journal of University Medical & Dental College, 2017)
Abstract Objective: The objective of this study was to examine the efficacy of Aquasonic gel and ketoprofen gel on pain and disability in the patients with nonspecific low back pain. Study design: The study design was experimental randomized trial,conducted at MadinahTeaching Hospital and Sugraha trust hospital Faisalabad . Method : In this study included 20 to 35 years age group both male and female. A convienient sampling technique of patients used visiting in physiotherapy department during months of Febraury-June 2016. Signed the informed consent forms and the privacy of patients will be taken into consideration. Two groups were made Group A was received ultrasound with Ketoprofen gel with strengthening and stretching exercises. Whereas Group B was received ultrasound with Aquasonic gel with strengthening and stretching exercises. Total treatment sessions were 10 consecutive days. The pain intensity was measured by visual analogue scale (VAS) and functional level was measured by Oswestry Disability Questionnaire (ODQ) before , mid and at the end of the treatment. Result: Pain mean was before treatment 5.65±0.58 in ketoprofen gel group and 5.70±0.79 in aquasonic gel group but after treatment mean reduced to 3.07± 0.77 in ketoprofen gel group and 5.08± 0.85 in aquasonic gel group. While functional level also improved in ketoprofen gel group after treatment as compared to aquasonic gel group. Conclusion: It could be concluded that ketoprofen gel phonophoresis with stretching and strengthening exercises is more effective than the aquasonic gel ultrasound in the management of non-specific lower lumbar back pain.